Höskuldur Thráinsson, Hjalmar P. Petersen, Jógvan í Lon Jacobsen & Zakaris Svabo Hansen (eds.) 2004: Faroese. An Overview and Reference Grammar - González Campo, Mariano (SELIM. Journal of the Spanish Society for Medieval English Language and Literature, 2019)
Sin resumen